Synergies between high‐energy satellites and ESO facilities. Issue 2 (27th April 2017) - Mainieri, V.
Abstract : High‐energy satellites, in particular XMM‐Newton, have clear synergies with ESO instruments. This is testified by the significant number of scientific publications based on data obtained with both facilities. In this article, we briefly review past synergies and discuss future possibilities.